Physical activity in Pakistani perspective: issues, implications, and recommendations - Muhammad Badar Habib; Muhammad Tahir Nazeer; Masood Mahfooz; Muhammad Shoaib Safdar (Journal of the Pakistan Medical Association, 2022)
It has been established that the benefits of physical activity on physical, psychological and social aspects of humans are substantially correlated with cardiovascular disorders, obesity, cancer, social anxieties and depressions, and enhanced socio-economic profile. In children and adolescents, physical activity has been correlated with academic achievements, social harmony and mental health. Similarly, in adults/old people, physical activity has been of variable benefits, bringing the chances of prolonged healthier lives. Though substantial work has been reported globally, there still is a paucity of literature in Pakistan regarding various aspects of physical activity. The current narrative review was planned to summarise the research work conducted in, or has emanated from, Pakistan in teens/college/school and university students, and adults from Pakistan on associated aspects of physical activity, ---Continue